Legal Services Baby Shower for Macias, Noxon, and Kahill Families - Watkins, Howard K. (1977)
Playing volleyball, Alice Mendoza serving, Gloria Escalante, Christina Russell, Doris Burnes, Christine Burnes (red tennis shoes), Charles Kahill, ?